Covalent triazine framework: Water treatment application. (August 2022) - Saputra, Edy; Prawiranegara, Barata Aditya; Sugesti, Heni; Nugraha, Muhammad Wahyu; Utama, Panca Setia
Abstract: Effective degradation of hazardous effluents from the water environment has become essential due to the face-paced growth of industrial wastewater. The covalent triazine frameworks (CTFs) is a promising advanced material that has been broadly utilized and demonstrated promising results in various water treatment applications. The notable superiority of CTFs compared to other advanced materials such as metal organic frameworks (MOFs) and covalent organic frameworks (COFs) is due to its triazine linkage architecture which absence of weaker bonds and a substantial amount of N content, making it adjustable surface area, porosity, electro-optical properties, and stability. CTFs have been developed for adsorptive removal, photocatalysis, and membrane filtration, exhibiting versatile applications. In this review paper, recent development, tunability design and strategy, and state-of-the-art applications of the CTF for wastewater treatment are discussed extensively. Graphical abstract: Unlabelled Image Highlights: A state of the art review of covalent triazine framework (CTF) for water treatment application Provides an in-depth analysis of CTF development Presents an overview of possible intensification pathways Discusses various aspects of using precursor building blocks